The Influence of Accounting System Regarding Accounting and Taxation of Entities - MATEȘ, Dorel; PUȘCAȘ, Adriana; URSACHI, Antonela; AJTAY, Eduard (Journal of Legal Studies, 2016)
Accounting and taxation in Romania at the beginning of the third millennium are in continuous development, as a result of globalization of the world economy and of connecting the accounting and tax system to the international and European one. The confluence of the two representative cultures – Anglo-Saxon and Latin-European – has left a strong mark on the Romanian accounting and taxation. The International Financial Reporting Standards (IFRS) and the European Directives set the line to follow for both the Romanian accounting and the Romanian taxation. We get to ask whether Romania has still got its own strategies of economic, social and cultural development or we are part of a system of strategies where accounting is also included?